IMPLIKASI YURIDIS PERATURAN PEMERINTAH NOMOR 2 TAHUN 2013 TENTANG PERUBAHAN ATAS PERATURAN PEMERINTAH NOMOR 63 TAHUN 2OO8 TENTANG PELAKSANAAN UNDANG.UNDANG TENTANG YAYASAN TERHADAP STATUS NAZHIR YAYASAN PESANTREN AL.MADINAH DI KOTA YOGYAKARTA - , Elan Kurniawan ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This thesis aims to determine the juridical implication of Government Regulation Number 2 year 2013 for Pesantren Al-Madinah Foundation has not been adjusted as a result of its articles of association under the provisions on its authority to manage waqf properties and determine the role of Pesantren Al- Madinah Foundation as nazhir in the governance of waqf properties in order to achieve the objectives of waqf. This study used the mix of juridical-normative and juridical-empirical study, is legal research which which promotes the secondary data (library research) and primary data (field research). This study was conducted at the office of Pesantren Al-Madinah Foundation in Yogyakarta City. The technique of collected data was done by non-random sampling with purposive sampling method. The results of the study were analyzed qualitatively and written with descriptive methods by describing and outlining in accordance with problems related to the study. The results showed that the juridical implication of Government Regulation Number 2 Year 2013 on Amendment to Government Regulation Number 63 Year 2008 concerning the Implementation of the Law on Foundations of the authority as nazhir for Pesantren Al-Madinah Foundation is currently still uses the word \"foundation\" in front of his name and has not adjusted its articles of association to the specified time limit is void ab initio so that the Foundation is not a legal entity nazhir in managing waqf property but as nazhir organization. However, based on the Government Regulation, Pesantren Al-Madinah Foundation enable to get the legal entity. In order to obtain status as a legal entity, then the foundation does not need to be dissolved and may apply for legalization of incorporation documents. Roles of Pesantren Al-Madinah Foundation as nazhir in governance waqf in Yogyakarta, namely coordination, consolidation, optimization of the waqf, and conduct guidance and supervision in the implementation of waqf properties.